THE SPIRITUAL CONNECTION BETWEEN THE CARTOGRAPHY OF THE HUMAN SUBCONSCIOUS AND THE STRUCTURES OF NEOLIBERAL THEOLOGY - Albert Camil Rath-Boșca (Agora International Journal of Economical Sciences (AIJES), 2024)
Usually, an economist, a manager, a business administrator, or any other participating member of the free market has a single and clear view of the pecuniary value of goods and the nature of capital. The logic of capitalism allows the economic agent to assign clear values to goods based on several factors. Although such a strict view of a good and its nature is mechanically correct, it is an incomplete one. Economists and economic theorists more broadly agree that commercial goods, whether they are directed to the consumer or intermediate goods in the production chain, are the result of human labour.
Keywords: 330